The Role of Circulating Regulatory T Cell Levels on Subclinical Atherosclerosis and Cardiovascular Risk Factors in Women with Systemic Lupus Erythematosus - Mario García-Carrasco; Pamela Soto-Santillán; Claudia Mendoza-Pinto; Rebeca González-Ramírez; Ana Lidia López-Carmona; Pamela Munguía-Realpozo; Ivet Etchegaray-Morales; Socorro Méndez-Martínez; José Luis Gálvez-Romero; Aurelio López-Colombo; Alejandro Ruiz-Arguelles (Mediators of Inflammation)
The increase in cardiovascular disease (CVD) in patients with systemic lupus erythematosus (SLE) is not fully explained by traditional CVD risk factors. Regulatory T cells (Treg cells) are considered atheroprotective. We investigated the relationship between the absolute number of different phenotypes of Treg cells and abnormal carotid intima-media thickness (IMT) in women with SLE. Sixty-six women with SLE with no history of CV disease were included. Carotid IMT was quantified by ultrasound. Abnormal carotid IMT was defined as ≥0.8 mm and two groups were compared according to this definition. Flow cytometry was used to analyze Foxp3 and Helios expression in peripheral blood CD4 T cells. A significantly higher level of absolute CD4+CD25+FoxP3high T cells was present in patients with abnormal carotid IMT compared with those without (1.795±4.182 cells/μl vs. 0.274±0.784 cells/μl; p=0.003). However, no correlations were found between any Treg cell phenotypes and carotid IMT. Only the absolute number of CD4+CD45RA+FoxP3low T cells was significantly decreased in SLE patients with low HDL cholesterol compared with those with normal HDL cholesterol (0.609±2.362 cells/μl vs. 1.802±4.647 cells/μl; p=0.009 and 15.358±11.608 cells/μl vs. 28.274±34.139; p=0.012, respectively). In conclusion, in SLE women, diminished levels of Treg cells based on flow cytometry were not a good indicator of abnormal carotid IMT.